On New Generalized Ostrowski Type Integral Inequalities. (22nd May 2014) - Qayyum, A.; Shoaib, M.; Matouk, A. E.; Latif, M. A.
Abstract : The Ostrowski inequality expresses bounds on the deviation of a function from its integral mean. The aim of this paper is to establish some new inequalities similar to the Ostrowski's inequality. The current paper obtains bounds for the deviation of a function from a combination of integral means over the end intervals covering the entire interval in terms of the norms of the second derivative of the function. Some new perturbed results are obtained. Application for cumulative distribution function is also discussed.